Hubungan Antara Inokulum Awal Patogen dengan Perkembangan Penyakit Hawar Upih pada Padi Varietas Ciherang - Bambang Nuryanto; Achmadi Priyatmojo; Bambang Hadisutrisno; Bambang Hendro Sunarminto (Universitas Gadjah Mada, 2010)
Study on the role of initial inoculums on disease development of rice sheath blight caused by Rhizoctonia solani Kühn was conducted in glass house at the Faculty of Agriculture University of Gadjah Mada from December of 2009 to July of 2010. The aim of this study was to evaluate the importance of sclerotia and mycelium in plant debris as primary inoculum form of R. solani. Results indicated that both sclerotia and mycelium in plant debris significantly affect the development of rice sheath blight. Disease severity was closely related to the number of sclerotia on rice plant. The highest disease severity was observed in plant inoculated with 10 sclerotia per hills. Treatments of 6 sclerotia and 5 g plant debris per hills had comparable effect on disease severity and area under disease progress curve of rice sheath blight. The results suggested that sclerotia and mycelia in plant debris might play a major role as primary inocula of the disease in rice growing field.